Flame retardant, thermal, and mechanical properties of glass fiber/nanoclay reinforced phenol–urea–formaldehyde foam. Issue 8 (16th March 2015) - Hu, Xiangming; Cheng, Weimin; Nie, Wen; Wang, Deming
Abstract : To increase the toughness, flame retardancy, and compression strength of phenolic foams, glass fiber/nanoclay composites were prepared, and their mechanical property, cellular structure, thermal stability, and flame retardancy were investigated. The results show that the pulverization rate of phenolic foam decreases significantly by adding glass fibers and nanoclay. The impact strength of the composite foam significantly increases with increasing quantities of glass fiber and nanoclay, while the compression strength of the composite foam first increases and then decreases. The microstructure of the composite foam indicates that excessive glass fiber increases the number of open cells, while an appropriate quantity of nanoclay can control the cell size. Further, excessive clay increases the thickness of cell walls and the percentage of open cells. Nanoclay increases the thermal stability of the composite foam; this decreases the maximum heat release rate, total heat release, and total smoke release of the foam, thus reducing its fire hazards. Glass fiber and nanoclay demonstrate good synergistic effects and significantly increase the compression strength, thermal stability, and flame retardancy of the foam. Moreover, the addition of nanoclay and glass fiber–nanoclay decreases the average aperture of the cells. POLYM. COMPOS., 37:2323–2332, 2016. © 2015 Society of Plastics Engineers